Cognitive Control and Flexibility in the Context of Stress and Depressive Symptoms: The Cognitive Control and Flexibility Questionnaire - Gabrys, Robert L.; Tabri, Nassim; Anisman, Hymie; Matheson, Kimberly (Frontiers in Psychology, 2018)
Cognitive control and (cognitive) flexibility play an important role in the ability to adapt to continuously changing environments. In addition to facilitating goal-directed behaviors, cognitive control and flexibility have been implicated in emotion regulation, and disturbances of these abilities were observed in mood and anxiety disorders. The reported studies examined the processes related to cognitive control and flexibility, emotional regulation and depressive symptoms, within the context of stressful experiences. To this end, a brief (18-item) self-report measure - the Cognitive Control and Flexibility Questionnaire (CCFQ) - was developed. This questionnaire measures the extent to which an individual is capable of exerting control over intrusive, unwanted (negative) thoughts and emotions in order to flexibly adapt and cope with a stressful situation. In Study 1, the CCFQ was assessed among both university students (N = 300) and a community sample (N = 302). Preliminary analyses suggested a stable and reliable two-factor structure, that of cognitive control over emotion, and appraisal and coping flexibility. Scores on the CCFQ were strongly associated with greater depressive symptoms, even after controlling for other measures that had been taken to reflect cognitive control and (in)flexibility (e.g., the Ruminative Response Scale; Perseverative Thinking Questionnaire). In Study 2 (N = 368), lower scores on the CCFQ were related to more negative stressor appraisals (i.e., greater perceived threat and uncontrollability) of a personally meaningful stressful event. Perceptions of threat and uncontrollability, in turn, partially accounted for the association between CCFQ subscale scores and depressive symptoms. The relation between lower CCFQ scores and heightened depressive symptoms was also partially accounted for by less frequent engagement in problem-focused coping and more use of emotion-focused methods. In Study 3 (N = 47 females), lower scores on the cognitive control over emotion component of the CCFQ predicted elevated negative affect and an exacerbated cortisol response following an acute psychosocial stressor (Trier Social Stress Test). The present research points to the CCFQ as a useful self-report tool to identify ways through which cognitive control and flexibility might be manifested in stressful situations, and how reductions in flexibility might be accompanied by elevated symptoms of depression.